Relation between monetary announcement and Phillips Curve? An empirical study from Malaysia - Philip, Abey (General Association of Economists From Romania (GAER), 2014)
Macro economist over the years have camped their argument on the tradeoff between inflation and unemployment on an economy. As the monetary announcement of an economy has an important influence on both inflation and unemployment, this paper reviews the existing literature to find out the relation between inflation and unemployment rate in Malaysia with special emphasis given on the monetary announcement over a period of 1980-2011. This research not only looks into the tradeoff between inflation and unemployment but also look into the impact of the monetary announcement in an economy. This research tries to look into the shape of the Phillips curve in Malaysian economy and how monetary announcement of Malaysia influence on the Phillips curve. This study can help the policy makers to come up with realistic policy to manage country’s inflation and unemployment rate with the support by monetary policy.